Effects of atorvastatin on the insulin resistance in women of polycystic ovary syndrome: A systematic review and meta-analysis. Issue 24 (18th June 2021) - Chen, Lin-Lin; Zheng, Jian-Hong
Abstract: Background: Atorvastatin treatment has been suggested as a therapeutic method for women with polycystic ovary syndrome (PCOS) in many clinical studies. Nonetheless, the effects of atorvastatin on insulin resistance in PCOS patients still remain controversial. Objective: The aim of this report was to evaluate the effects of atorvastatin therapy on the insulin resistance in the treatment of PCOS compared to that of placebo, in order to confer a reference for clinical practice. Methods: Randomized controlled trials (RCTs) of atorvastatin for PCOS published up to August, 2020 were searched. Standardized mean difference (SMD) and 95% confidence interval (CI) were calculated, and heterogeneity was measured by the I 2 test. Sensitivity analysis was also carried out. The outcomes of interest were as follows: fasting glucose concentration, fasting insulin level, homeostasis model assessment of insulin resistance (HOMA-IR) or body mass index (BMI) value. Results: Nine RCTs with 406 participants were included. The difference of fasting glucose concentration in PCOS patients between atorvastatin group and placebo group was not statistically significant (8 trials; SMD −0.06, 95% CI −0.31 to 0.20, P  = .66). PCOS patients in atorvastatin group had lower fasting insulin level than those in placebo group (7 trials; SMD −1.84, 95% CI −3.06 to −0.62, P  < .003). The homeostasis model assessment of insulin resistance (HOMA-IR) value showed significant decrease in the atorvastatin therapy compared to placebo (6 trials; SMD −4.12, 95% CI −6.00 to −2.23, P  < .0001). In contrast to placebo, atorvastatin therapy did not decrease the BMI value significantly in PCOS patients (7 trials; SMD 0.12, 95% CI −0.07 to 0.31, P  = .22). Conclusions: Atorvastatin therapy can reduce insulin resistance in the treatment of patients with PCOS. In addition, further large-sample, multi-center RCTs are needed to identify these findings.